Lease of Pier VII as a Rudiment of the Single Port System - Trupac, Igor (Promet - Traffic&Transportation, 2003)
The fact that both ports, Koper and Trieste, share the sameprofile - universal ports with specialized terminals (except foroil and bulk cargoes), leaves way to two possible scenarios: eitheran exhausting competitive struggle between them, or anagreement on work sharing and specialization, which shouldgradually result in a single port system. Such consideration willbecome even more topical after Slovenia ’s accession to the EU.In the long run it is therefore sensible to consider Koper with itsport as a joint nucleus with Trieste - of a large continental .systemgravitating to the central part of the North Adriatic.This paper sets out to help understand such a course by: 1)reviewing the current state of the development of transportationin the Mediterranean and in Europe, 2) assessing the potentialbenefits of such system, and 3) assessing the barriers and opportunitiesfor its implementation.